PENINGKATAN KARAKTER ISLAMI BAGI PESERTA DIDIK DI LINGKUNGAN SEKOLAH MENENGAH ATAS NEGERI 3 KOTA TANGERANG SELATAN - Muhammad Muhyidin (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2021)
In general, this study aims to determine the increase in Islamic character in SMAN 3 Kota Tangerang Selatan based on activities carried out at school. This study uses the phenomenology method, which is a study of visible and real phenomena, by collecting data and information through interviews and observations to the main informants, namely the principal, teachers and class XI students. While the data analysis used descriptive qualitative analysis in the form of exposure to the results of interviews, observations and supplemented with data obtained from supporting documents. The findings in this study are an increase in discipline of dzuhur and asr prayers in congregation at school, increased activity and order in participating in duha and tadarus prayers together, increasing Islamic spiritual activities (majlis ta'lim) at school, and increasing other religious activities at home. which can be seen from the worship monitoring sheet